2017
DOI: 10.1038/s41598-017-13326-y
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-Laced Biomimetic Material Stimulation of Bone Marrow Derived Mesenchymal Stem Cells to Promote Osteogenic Effects

Abstract: A hydroxyapatite-collagen (HC) composite material can mimic composition and ultra-structures of natural bone and provide adequate bioactive material-tissue interactions. Incorporation of dopamine (DA) is one of keys in increasing the mechanical strength of the HC material to approaching that of cortical bone. In this study, the in vitro osteogenic effects of polydopamine-laced hydroxyapatite collagen calcium silicate (HCCS-PDA) were examined by culturing rat mesenchymal stem cells (rMSCs) on HCCS-PDA and HCCS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…In a previous study, HCCS‐PDA in particle form was tested for bone regeneration capacity both in vitro and in vivo to observe sole effect of HCCS‐PDA material. The results showed that the HCCS‐PDA enhanced local bone formation in calvarial CSD model, forming tight interface between HCCS‐PDA particle and newly formed bone . With well‐designed scaffold, the amount of bone regeneration is expected to increase.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a previous study, HCCS‐PDA in particle form was tested for bone regeneration capacity both in vitro and in vivo to observe sole effect of HCCS‐PDA material. The results showed that the HCCS‐PDA enhanced local bone formation in calvarial CSD model, forming tight interface between HCCS‐PDA particle and newly formed bone . With well‐designed scaffold, the amount of bone regeneration is expected to increase.…”
Section: Introductionmentioning
confidence: 98%
“…The results showed that the HCCS-PDA enhanced local bone formation in calvarial CSD model, forming tight interface between HCCS-PDA particle and newly formed bone. 2 With well-designed scaffold, the amount of bone regeneration is expected to increase. Computeraided design (CAD) modelling has enabled precise control of the scaffold architecture, including the pore size, connectivity, dimensions and shape.…”
mentioning
confidence: 99%
“…Bliziotes et al (2000) showed that the deletion of the DA transporter gene in mice reduces the cancellous bone mass. Moreover, DA promotes osteoblastic differentiation of murine preosteoblasts (Lee et al, 2015) and rat bone marrow mesenchymal stem cells (MSCs; Lee, Lee, Zou, Daniel, & Ko, 2017).…”
mentioning
confidence: 99%
“…From our Prestoblue ® assay and cytoskeleton results, it was observed that PDA coating significantly up-regulates WJMSCs proliferation. Even though we are still unsure of the exact mechanism behind this explanation, it can be hypothesized that the ions dissolved and released from our PDA-coated cements were able to positively modulate cell behaviors through the synergistic combinations between the functional groups present in PDA, and the presence of ionic components on the coating surfaces [ 47 , 48 ]. Moreover, we believed that some WJMSC had begun to enter the stage of osteogenesis differentiation, so the growth rate of the cells would gradually slow.…”
Section: Resultsmentioning
confidence: 99%